Jumping to conclusions: The psychology of delusional reasoning - Garety, P; Freeman, D; Jolley, S; Ross, K; Waller, H; Dunn, G (2011)
Delusions are a key symptom of psychosis and they are frequently distressing and disabling. Existing treatments, both pharmacological and psychological, are only partially effective. It is important to develop new treatment approaches based on theoretically derived and empirically tested processes. Delusions are associated with a reasoning bias: the jumping to conclusions (JTC) bias involves gathering limited information to reach decisions. It is proposed that this bias influences appraisals of psychotic experiences leading to the formation and persistence of delusions. Existing treatments do not influence JTC. A new intensive treatment approach - 'reasoning training' - is described. It aims to encourage participants to gather information, consider alternative explanations for events and review the evidence before reaching a decision. Preliminary data suggest that it is possible to change the JTC bias and that this improves belief flexibility and may reduce delusional conviction. The concepts and methods of this new approach have implications for clinical practice.